The dragon-II simulations: I. Evolution of single and binary compact objects in star clusters with up to 1 million stars - Arca Sedda, Manuel; Kamlah, Albrecht; Spurzem, Rainer; Giersz, Mirek; Berczik, Peter; Rastello, Sara; Iorio, Giuliano; Mapelli, Michela; Gatto, Massimiliano; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2024)
We present the first results of the Dragon-II simulations, a suite of 19 N-body simulations of star clusters with up to 106 stars, with up to 33 per cent of them initially paired in binaries. In this work, we describe the main evolution of the clusters and their compact objects (COs). All Dragon-II clusters form in their centre a black hole (BH) subsystem with a density 10−100 times larger than the stellar density, with the cluster core containing 50-80 per cent of the whole BH population. In all models, the BH average mass steeply decreases as a consequence of BH burning, reaching values 〈mBH〉< 15 M⊙ within 10−30 relaxation times. Generally, our clusters retain only BHs lighter than 30 M⊙ over 30 relaxation times. Looser clusters retain a higher binary fraction, because in such environments binaries are less likely disrupted by dynamical encounters. We find that BH-main-sequence star binaries have properties similar to recently observed systems. Double CO binaries (DCOBs) ejected from the cluster exhibit larger mass ratios and heavier primary masses than ejected binaries hosting single CO binaries (SCOBs). Ejected SCOBs have BH masses mBH = 3−20 M⊙, definitely lower than those in DCOBs (mBH = 10−100 M⊙).
Vorab online veröffentlicht: 09 January 2024
Gesehen am 03.07.2024